Balanço de fósforo em 12 anos e estratégias de culturas anuais para acessar reservas de fósforo construídas ao longo de 15 anos por fontes orgânicas e mineral - Marchezan, Carina (2022)
The agricultural production system of Brazil and other countries is highly dependent on imports of phosphate fertilizers. The quantification and long-term impact of secondary P sources, such as residues from livestock production and the access to P reserves in agricultural soils by plants is of common interest and is an alternative to decrease the use of mineral phosphate fertilizers. This Thesis aimed to evaluate the long-term impact of different fertilizer sources and changes in soil P reserves and to investigate the strategies used by annual plants to access and increase P availability in the rhizosphere. To this end, we conducted three studies (Chapters I, II and III) in a long-term experiment, implemented in 2004, under an arhenic dystrophic red Argissolo Vermelho, in Santa Maria (RS). The treatments used were liquid swine manure, liquid bovine manure, overlapping pig litter mineral fertilizer and a control treatment, without the application of nutrients. In Chapter I, we determined the efficiency of the P balance in the system, by accounting the inputs, outputs and stock of this element in the soil over 12 years of cultivation. The accumulated P forms in the soil profile were determined by means of the sequential chemical P fractionation technique. In Chapter II, we selected 3 treatments (liquid swine manure, mineral fertilizer and control) and investigated changes in the root system of corn roots and their relationship with P uptake and utilization efficiency. For this, we installed acrylic minirizotron tubes and monitored, in situ, the root growth dynamics. Root morphological parameters were determined and correlated with physiological P utilization and crop productivity variables. Finally, in Chapter III, we subjected the treatments discussed in Chapter II to AMF inoculation with the species Rhizophagus intraradices (Rootella BR). In the soil were the contents of P, N and C contained in the microbial biomass and soil, as well as the activity of the enzyme acid phosphatase and β-glucosidase. These variables were related to the availability of P in the rhizosphere and its uptake by corn and oat plants. Animal waste applications, especially those of pigs, generate large reserves of P in soils. The large accumulation of P in these soils decreases the efficiency of the P mass balance. Plants grown in soils with P reserves built up with swine manure application showed lower values of root morphological variables. On the other hand, in the rhizospheric soil they presented higher P availability, enzyme activity and flux of C, N and P in biomass that are highly correlated with higher P uptake and biomass production by plants. Plants grown in soil with the application of mineral fertilizer showed higher values of morphological variables of roots but showed no difference in P availability between rhizospheric and bulk soil. The plants grown in the control soil presented morphological values close to those presented by the plants grown in the soil with application of mineral fertilizer. However, the biomass production of these plants was much lower.